MEMBERSHIP STATUS OF TIMOR LESTE IN ASEAN BASED ON ASEAN CHARTER 2007: PROBLEM AND PROSPECT - Rifqi Mahardika Putra; Calvina Chaeria Ramadhany; Sofiyanti Salsabila (International Law Department, Faculty of Law Universitas Padjadjaran, 2021)
As the youngest country in Southeast Asia, Timor Leste realizes that becoming a member of ASEAN is important, and even the Timor Leste government says joining ASEAN is a priority for the country. Following up on its seriousness, in 2011, Timor Leste officially submitted an application to become a member of ASEAN, but 11 years later, the application has not yet been approved. Based on this background, this study was conducted to determine the current status of Timor Leste's membership in ASEAN based on the ASEAN Charter 2007 and to find out what hinders Timor Leste's acceptance as a member of ASEAN and how the prospects for Timor Leste's membership in ASEAN in the future. The results of this study show that first, in terms of Article 6 paragraph 2 of the ASEAN Charter, Timor Leste's membership status in ASEAN has not been ratified because Timor Leste has not fulfilled all the requirements contained in the article so currently, it is still a non-member observer country. Second, the thing that hinders Timor Leste's acceptance as a member of ASEAN is the use of a rigid and absolute consensus as well as the growing era which makes ASEAN countries increasingly see many factors to accept Timor Leste, then seen from Timor Leste's economic growth which is the slowest in Southeast Asia and one of the poorest countries in the world makes the authors feel that Timor Leste's membership status in ASEAN will not be accepted in the near future.